2023
DOI: 10.3390/catal13030457
|View full text |Cite
|
Sign up to set email alerts
|

The Quick Removal of Toxic Dye Molecules by an Efficient Adsorptive BiOI/Bi2MoO6 Heterostructure

Abstract: Adsorption is a low-energy, economical, and efficient method for pollutant removal from water. Because of their unique structure, large specific surface area (SSA), and non-toxicity, bismuth-based semiconductors, usually researched for the photodegradation of organic molecules, are also excellent for dark adsorption processes. Here, a three-dimensional adsorbent with a heterostructure with a hydrangea-like shape made of Bi2MoO6 (BMO) and BiOI (BOI) was synthesized by a one-pot solvothermal process and investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…R 2 values of the two models showed that experimental data fitted better with the Langmuir isotherm model, indicating that both DPC and Cr(VI) are bound to homogeneously distributed sites onto a monolayer of the support materials (Table S2). 60 According to eq 4, the q m values of WCF for DPC and Cr(VI) were 19.32 and 8.38 mg/g, respectively. The q m value of cWCF for DPC was 32.57 and 37.34 mg/g for Cr(VI).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…R 2 values of the two models showed that experimental data fitted better with the Langmuir isotherm model, indicating that both DPC and Cr(VI) are bound to homogeneously distributed sites onto a monolayer of the support materials (Table S2). 60 According to eq 4, the q m values of WCF for DPC and Cr(VI) were 19.32 and 8.38 mg/g, respectively. The q m value of cWCF for DPC was 32.57 and 37.34 mg/g for Cr(VI).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Bismuth molybdate (BMO) is a low-cost and low-toxicity bimetallic oxide with an adjustable morphology and good catalytic properties. Because of these characteristics, it has been studied for a wide range of applications including as an acousto-optic nanomaterial, gas sensor, photoconductor, photocatalyst, adsorbent, ionic conductor, metabolite, and humidity sensor. As a gas sensor, the α and γ phases of BMO have been developed to detect different VOC, but never specifically for TEA quantification. , This Aurivillius oxide is commonly synthesized by combining bismuth­(III) nitrate (BNO) with either ammonium heptamolybdate or sodium molybdate. , More recently, BMO has been derived from Bi-MOF instead of uncoordinated BNO . This synthesis method was shown to improve the performance of BMO nanoparticles for photocatalysis due to better charge separation mainly caused by the presence of intrinsic surface defects generated by the collapse of the MOF structure .…”
Section: Introductionmentioning
confidence: 99%